Modification Effect of Carbon Nanotubes by LiCl (CNTs/LiCl) on the Electrical Conductivity Character - Yuliastuti, Indri; Pardoyo, Pardoyo; Subagio, Agus (JURNAL SAINS DAN MATEMATIKA, 2015)
Carbon nanotubes have been modified by mass percentage variation of LiCl using reflux method. Mass percentage variation used in this study was 0, 1, 5, and 15%. The purpose of this study was to determine the effect of LiCl dope on the electrical conductivity of carbon nanotubes. This research was used reflux method by heating at 80Â°C for 24 h. The products produced were in the form of CNTs / LiCl dry powders. The characterization results of FT-IR spectroscopy showed that there was a Li-O bond group in the addition of 1, 5, and 15% LiCl while XRD characterization results did not show any diffraction of lithium chloride. The results of this study showed an increase in electrical conductivity at 15% addition of LiCl which was of 2.69 x 10-3 S/m. Electrical conductivity in the addition of 1% and 5% LiCl decreased (1.17 x 10-6 S/m and 2.64 x 10-6 S/m) from CNTs/LiCl 0% (3.68 x 10-6 S/m) due to the influence of the PVA high resistivity used as an adhesive in the pellets fabrication.